The Influence of BOPO, LDR/LFR, and NPL on the Profitability of Core Capital Bank Group (KBMI) 1 Banks During the Covid-19 Pandemic - Sutardiyanta, Ihwan; Nugraha, Nugraha (Accounthink : Journal of Accounting and Finance, 2024)
This study aims to evaluate the impact of the Operational Costs to Operating Income ratio (BOPO), Loan to Deposit Ratio (LDR), and Non-Performing Loans (NPL) on Profitability, measured through the Return On Assets (ROA) and Net Profit Margin (NPM) ratios of Bank KBMI 1 during the Covid-19 pandemic period spanning from 2020 to 2023. The research encompassed 28 companies affiliated with Bank KBMI 1/BUKU 1 as the population, and 25 companies were chosen as samples using purposive sampling techniques. The analysis was conducted through multiple linear regression on a dataset comprising 75 time series. The findings of the research indicate that: (1) BOPO exhibits a negative and statistically significant influence on profitability, encompassing both ROA and NPM, (2) NPL and LDR/LFR do not wield a significant impact on profitability, be it ROA or NPM. Consequently, in totality, BOPO, LDR/LFR, and NPL collectively contribute to influencing profitability.